APPRAISAL DEVICES AS A MEANS TO DISCLOSE IDEOLOGICAL STANCE - , Warsono (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2008)
Abstract This article describes the results of analyzing a text entitled “Al-Qaeda in the Asia Pacific: Origin, Capability, and Threat” in order to find out how the text writer uses appraisal devices to present his stance towards the subject of the text he is writing. Appraisal devices include systems of attitude (comprising system of affect, system of judgment, and system of appreciation), system of amplification, and the source of attitude (Martin and Rose, 2003). Text analysis follows the procedure suggested by White (2001) by applying the Appraisal Systems offered by Martin and Rose (2003). The results of text analyses show that the text writer has strong negative feelings about the subject of the text he is writing, which is Al-Qaeda, and as a consequence he also has strong negative judgment as well as strong negative appreciation about it. It can be concluded that the writer’s stance or attitude towards Al-Qaeda, the subject his text, is strongly negative, that is, he believes that Al-Qaeda is an evil and dangerous organization. In presenting his stance towards the subject of the text he is writing, the writer gives preference to the use of the system of affect, followed by the use of the system of judgement, and finally the use of appreciation system. To show the strength of his feelings towards the subject of the text, the writer prefers the use of amplifying force to the use of sharpening or softening focus. Out of the four options that the amplification system provides to amplify the force (i.e. intensifier, attitudinal lexis, metaphor, and swearing), the writer gives preference to the use of attitudinal lexis.